(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was undertaken to record the productive and reproductive performance of T&D and cross-bred (T&D X Assam Local) pigs under field condition of Assam. A total of 5 numbers of farmers were selected randomly and purposively on the basis of their experience in pig farming and who must possessed at least 3 numbers of T&D and 3 numbers of cross-bred pigs with one male and two females of each genetic groups of pig. The pigs were reared under free range scavenging system of rearing. The piglets were monitored regularly for their health status and their monthly body weight was recorded up to 9 months of age. Some of the important reproductive traits such as age at puberty (days), body weight at puberty (kg.), age at first farrowing, gestation period (days), litter size, body weight of piglets at birth (kg.), pre-weaned litter survivability (%), farrowing intervals (days) and body weight at 12 months of age (kg.) were also recorded. From the above study it may be inferred that T&D pigs are significantly better in terms of productive and reproductive performance than cross-bred under field condition of Assam.